Management of spontaneous pneumothorax and postinterventional pneumothorax: German S3-guideline = S3-Leitlinie : Diagnostik und Therapie von Spontanpneumothorax und postinterventionellem Pneumothorax - Schnell, Jost; Beer, Meinrad; Eggeling, Stephan; Gesierich, Wolfgang; Gottlieb, Jens Tobias; Herth, Felix; Hofmann, Hans-Stefan; Jany, Berthold; Kreuter, Michael; Ley-Zaporozhan, Julia; Scheubel, Robert; Walles, Thorsten; et al. (Zentralblatt für Chirurgie, 2018)
In Germany, 10,000 cases of spontaneous pneumothorax are treated inpatient every year. The German Society for Thoracic Surgery (DGT), in co-operation with the German Society for Pulmonology (DGP), the German Radiological Society (DRG) and the German Society of Internal Medicine (DGIM) has developed an S3 guideline on spontaneous pneumothorax and postinterventional pneumothorax moderated by the German Association of Scientific Medical Societies (AWMF). Method Based on the source guideline of the British Thoracic Society (BTS2010) for spontaneous pneumothorax, a literature search on spontaneous pneumothorax was carried out from 2008 onwards, for post-interventional pneumothorax from 1960 onwards. Evidence levels according to the Oxford Center for Evidence-Based Medicine (2011) were assigned to the relevant studies found. Recommendations according to GRADE (A: “we recommend”/“we do not recommend”, B: “we suggest”/“we do not suggest”) were determined in three consensus conferences by the nominal group process. Results The algorithms for primary and secondary pneumothorax differ in the indication for CT scan as well as in the indication for chest drainage application and video-assisted thoracic surgery (VATS). Indication for surgery is recommended individually taking into account the risk of recurrence, life circumstances, patient preferences and procedure risks. For some forms of secondary pneumothorax, a reserved indication for surgery is recommended. Therapy of postinterventional spontaneous pneumothorax is similar to that of primary spontaneous pneumothorax. Discussion The recommendations of the S3 Guideline provide assistance in managing spontaneous pneumothorax and post-interventional pneumothorax. Whether this will affect existing deviant diagnostic and therapeutic measures will be demonstrated by future epidemiological studies.